Environmental Perspectives in John Nkemngong Nkengasong’s God was African - Gola, Nfon Rita; Ngongkum, Eunice (Advances in Social Sciences Research Journal, 2025)
The paper deliberates on forms of environmental representations in John Nkemngong Nkengasong’s God was African (2015), with the aim of unraveling the unsaid. It interrogates the word environment as an inclusive term whose diverse forms interact with humans to the generation of complex stories. Guided by the argument that environments are fragmented by time, geography and forms of nature, the paper questions the effectiveness of modern cultural trends as developmental voices for Africa. It x-rays culture as that materiality from which all else develops. Within this cultural materialist frame it applauds the nature/culture unison of traditional Africa but queries the nature/culture divide typical of the modern African state. It unveils in God was African’s nuanced tensions between tradition and modernity evidences of the lapses of a dialogic cultural criticism for Postcolonial Africa. It thus advocates the evolvement of a constructivist cultural frame in celebration of Africa’s transcultural space exemplified by God was African’s Lewoh setting. Postcolonial ecocriticism, for its commitment to the ecological, political and social concerns of the once colonized spaces gains ground as analytical tool.